Clinical trial on effectiveness of Hingwashtaka Arka drops in the management of infantile colic - Navami, B; Mallannavar, Vijaylaxmi; Anjali, Anjali (Journal of Ayurveda and Holistic Medicine (JAHM), 2023)
Background: Infantile colic is a typical pediatric disorder in which persistent or excessive crying is one of the most distressing problems of infancy. Infantile abdominal colic is episodes of crying for more than three hours a day or more than three days in a week. Colic begins at about 2 to 3 weeks of age and ends between 3 to 24 months. Objective: To evaluate the effect of Hingwasthaka Arka Drops administered per orally for 7 days in infants between the age group of 2-6 months suffering from Infantile colic Method: This study is open labelled single arm prospective clinical trial. Hingwasthaka Arka (a liquid preparation obtained through distillation) drops 1ml thrice a day before feeding for 7 days orally. Methodology: it was a single group clinical study with pre and post design. Pretest assessment of subjective parameters was done using FLACC scale and other associated features on day 1 day 4 and day 7 of the treatment. Results and conclusion: The study has shown statistically significant reduction in the subjective parameters with the P value 0.005. hence it was inferred that the intervention selected for the present study Hingwashtaka arka drops is effective in the management of infantile colic in 2-6 months.